Switchgrass Biomass Composition Traits and their Effects on its Digestion by Ruminants and Bioconversion to Ethanol. Issue 1 (10th November 2016) - Vogel, Kenneth P.; Casler, Michael D.; Dien, Bruce S.
Abstract : Six generations of divergent breeding in switchgrass ( Panicum virgatum L.) for forage in vitro digestibility (IVDMD) resulted in significant changes in 20 biomass composition traits. Stepwise multiregression was used to determine which of the 20 composition traits had the largest significant effects on forage IVDMD and potential ethanol yield (ETOH) in a biorefinery. Switchgrass biomass samples from a field nursery containing the divergent switchgrass populations and families were harvested after flowering, dried, ground, and analyzed for composition traits by near‐infrared reflectance analyses using previously developed near‐infrared reflectance calibrations. After nonsignificant variables were eliminated, the resulting multiple regression models were highly significant ( P < 0.001) and accounted for 95 and 96%, respectively, of the total variation for both IVDMD and ETOH. Standardized partial regression coefficients were used to estimate the relative importance of each significant variable. The biomass composition factors that had the largest impact on both IVDMD and ETOH were esterified ferulates, p ‐coumarate esters, specific cell wall sugars that are involved in the linkage of cell wall lignin to hemicellulose, N, and extracted fats. Klason lignin was not a significant variable in either regression analysis, even though it was strongly negatively correlated with both IVDMD and ETOH. The IVDMD test, which acted as a biological selection index in a long‐term population breeding program, impacted an array of switchgrass biomass composition traits whose relative effects on both IVDMD and ETOH had not been previously quantified.